An experimental investigation into multi-scale damage progression in laminated composites in bending. (1st August 2016) - Mortell, D.J.; Tanner, D.A.; McCarthy, C.T.
Abstract: In laminated composite materials fibre–matrix debonding, as an initial damage mechanism, can initiate a damage sequence that can result in catastrophic failure of its structure by promoting intermediate damage mechanisms. This paper presents an in-depth experimental investigation into each of these damage mechanisms and how they transition from one state to the next, beginning at the micro-scale with fibre–matrix debonding and crack coalescence, to transverse ply fracture at the meso-scale through to formation of macroscopic delamination. In-situ SEM micro-mechanical testing is used to determine the onset of the aforementioned damage mechanisms and to follow their progression in laminates of both [0/90]s and [90/0]s stacking sequences. The damage progression of [0/90]s specimens is presented first, followed by the more progressive failure of [90/0]s specimens, yielding an in-depth analysis of both rapid and more progressive damage growth, respectively. The intralaminar cracking and delamination of [0/90]s laminates was found to be instantaneous and provided limited opportunity to characterise damage progression. For [90/0]s laminates, damage progression was much more progressive and various factors such as fibre positioning were shown to influence debonding initiation and crack path development before catastrophic failure and so these laminates form the bulk of the analysis presented for this paper.